Crassulacean Acid Metabolism Abiotic Stress-Responsive Transcription Factors: a Potential Genetic Engineering Approach for Improving Crop Tolerance to Abiotic Stress - Amin, Atia B.; Rathnayake, Kumudu N.; Yim, Won C.; Garcia, Travis M.; Wone, Beate; Cushman, John C.; Wone, Bernard W. M. (Frontiers in Plant Science, 2019)
This perspective paper explores the utilization of abiotic stress-responsive transcription factors (TFs) from crassulacean acid metabolism (CAM) plants to improve abiotic stress tolerance in crop plants. CAM is a specialized type of photosynthetic adaptation that enhances water-use efficiency (WUE) by shifting CO2 uptake to all or part of the nighttime when evaporative water losses are minimal. Recent studies have shown that transcription factor-based genetic engineering could be a useful approach for improving plant abiotic stress tolerance because of the role of transcription factors (TFs) as master regulators of clusters of stress-responsive genes. Here, we explore the use of abiotic stress-responsive TFs from CAM plants to improve abiotic stress tolerance and WUE in crops by controlling the expression of gene cohorts that mediate drought-responsive adaptations. Recent research has revealed several transcription factor families including AP2/ERF, MYB, WRKY, NAC, NF-Y, and bZIP that might regulate water-deficit stress responses and CAM in the inducible CAM plant Mesembryanthemum crystallinum under water-deficit stress-induced CAM and in the obligate CAM plant Kalanchoe fedtschenkoi. Overexpression of genes from these families in Arabidopsis thaliana can improve abiotic stress tolerance in A. thaliana in some instances. Therefore, we propose that TF-based genetic engineering with a small number of CAM abiotic stress-responsive TFs will be a promising strategy for improving abiotic stress tolerance and WUE in crop plants in a projected hotter and drier landscape in the 21st-century and beyond.